Conservation benefits of a large marine protected area network that spans multiple ecosystems. - Smith JG; Lopazanski C; Free CM; Brun J; Anderson C; Carr MH; Claudet J; Dugan JE; Eurich JG; Francis TB; Gill DA; Hamilton SL; et al. (Wiley Periodicals LLC on behalf of Society for Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long-term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta-analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no-take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.
Keywords: California; arrecifes rocosos; biodiversidad oceánica; bosques de algas; fisheries; kelp forests; marine reserve; ocean biodiversity; pesquerías; reserva marina; rocky reefs; surf zone; zona de oleaje; 冲浪区; 加利福尼亚; 岩礁; 海洋保护区; 海洋生物多样性; 海藻林; 渔业